ARP Case Report Nº 12: Communicating Varix between the Left Renal Vein and Left Ascending Lumbar Vein - Silva, Carlos Francisco (2018)
69-year-old female found on a routine radiological follow-up (yearly abdominal CT scan) after a left adrenalectomy 4 years ago (pathologically proven cortical adenoma). Chronic left flank pain, already present before the adrenalectomy was the major complaint. A small left para-aortic “mass” was the main finding on the CT scan. As differential diagnosis we have considered para-aortic lymphadenopathy, adrenal mass or a saccular renal artery aneurysm given a somewhat prominent contrast enhancement. This patient had previous abdominal CT scans, one before the adrenalectomy and the others after that surgery, and in all but one of them it was retrospectively shown that this “mass” was already present. Coronal and oblique axial views and MIP reconstruction better depicted that the “mass” was indeed a varix or varicosity that put into communication the left renal vein and the left ascending lumbar vein. Literature review have shown that this varix could be an explanation for the chronic left pain that this patient had because of the compression and irritation of the left lumbar plexus given the close relation of these two anatomical structures. The “disappearance” or transitory collapse of this varix in one of the patient´s previous follow-up CT scans that we retrospectively analyzed might be due to variations in intra-abdominal pressure related to Valsalva maneuver during the CT scan image acquisition. After alerting the requesting physicians to this varix and possible explanation for the chronic pain complaints, the patient was referred to Pain Medicine specialty in our institution.